Immunological Impact of a Gluten-Free Dairy-Free Diet in Children With Kidney Disease: A Feasibility Study - Pérez-Sáez, María José; Uffing, Audrey; Leon, Juliette; Murakami, Naoka; Watanabe, Andreia; Borges, Thiago J.; Sabbisetti, Venkata S.; Cureton, Pamela; Kenyon, Victoria; Keating, Leigh; Yee, Karen; Fernandes Satiro, Carla Aline; et al. (Frontiers in Immunology, 2021)
Kidney disease affects 10% of the world population and is associated with increased mortality. Steroid-resistant nephrotic syndrome (SRNS) is a leading cause of end-stage kidney disease in children, often failing standard immunosuppression. Here, we report the results of a prospective study to investigate the immunological impact and safety of a gluten-free and dairy-free (GF/DF) diet in children with SRNS. The study was organized as a four-week summer camp implementing a strict GF/DF diet with prospective collection of blood, urine and stool in addition to whole exome sequencing WES of DNA of participants. Using flow cytometry, proteomic assays and microbiome metagenomics, we show that GF/DF diet had a major anti-inflammatory effect in all participants both at the protein and cellular level with 4-fold increase in T regulatory/T helper 17 cells ratio and the promotion of a favorable regulatory gut microbiota. Overall, GF/DF can have a significant anti-inflammatory effect in children with SRNS and further trials are warranted to investigate this potential dietary intervention in children with SRNS.